2015
DOI: 10.3802/jgo.2015.26.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of para-aortic lymphadenectomy before chemoradiotherapy in locally advanced cervical cancer

Abstract: ObjectiveTo evaluate the cost-effectiveness of nodal staging surgery before chemoradiotherapy (CRT) for locally advanced cervical cancer in the era of positron emission tomography/computed tomography (PET/CT).MethodsA modified Markov model was constructed to evaluate the cost-effectiveness of para-aortic staging surgery before definite CRT when no uptake is recorded in the para-aortic lymph nodes (PALN) on PET/CT. Survival and complication rates were estimated based on the published literature. Cost data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
(31 reference statements)
1
15
0
Order By: Relevance
“… 2 4 9 12 25 The surgical approach used in the Uterus-11 trial was conventional laparoscopy extending to the renal vessels in 96.6% of patients. Furthermore, Lee et al showed that nodal staging surgery before definitive chemoradiation may be cost effective, especially in patients with negative PET-CT. 27 Well-designed randomized trials comparing PET-CT with surgical staging (PALDISC trial) are ongoing. 28 Minimally invasive surgical staging in patients with locally advanced cervical cancer has demonstrated upstaging rates between 22% and 43% compared with clinical staging.…”
Section: Discussionmentioning
confidence: 99%
“… 2 4 9 12 25 The surgical approach used in the Uterus-11 trial was conventional laparoscopy extending to the renal vessels in 96.6% of patients. Furthermore, Lee et al showed that nodal staging surgery before definitive chemoradiation may be cost effective, especially in patients with negative PET-CT. 27 Well-designed randomized trials comparing PET-CT with surgical staging (PALDISC trial) are ongoing. 28 Minimally invasive surgical staging in patients with locally advanced cervical cancer has demonstrated upstaging rates between 22% and 43% compared with clinical staging.…”
Section: Discussionmentioning
confidence: 99%
“…Another attempt to perform paraaortic lymphadenectomy before chemoradiotherapy in late cervical cancer is considered effective to improve survival only in patients who have not had an enlarged paraaortic lymph node. However, it has little to no difference in patients with enlarged paraaortic lymph nodes 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This was followed later by an analysis of risk factors, and then the choice between primary surgery or chemoradiation (radiotherapy combined with chemotherapy RCTX, extended to encompass the para-aortic region). This strategy of risk factor analysis was more cost-effective than either primary surgery or primary chemoradiation [ 22 , 23 ]. Although the best results are obtained when PET or CT scan substitutes for surgical staging, the final results of imaging are not yet satisfactory for formulating a proper management plan, especially when it comes to determining the radiation field.…”
Section: Discussionmentioning
confidence: 99%
“…have suggested that surgical staging of para-aortic nodes are cost-effective methods, while a PET or CT scan does not reveal the presence of lymph node metastases in LACC patients. In 10% of cases, the para-aortic nodes are involved, even though the PET or CT scan is negative [ 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%